PEMANFAATAN LIMBAH SAYUR, MAKANAN DAN JERAMI PADI DENGAN BIOAKTIVATOR Trichoderma sp. SEBAGAI MEDIA TANAM BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN AWAL - Vira Irmasari; Eko Pangestu; Jojon Soesatrijo (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2023)
Alternative growing media are needed to overcome the shortage of top soil which generally occurs in oil palm nursery. Organic waste such as vegetables, food and rice straw is one of the ingredients that can be used as a growing medium because it is easy to find and has a high nutrient content. These wastes need to be decomposed to make them more easily absorbed by plants, therefore it is necessary to add bioactivators such as Trichoderma sp. for speed up the decomposition process. The purpose of this study are to obtain alternative growing media for organic waste, determine its effect on oil palm seedlings, and determine the best growing media treatment. This research conducted at experiment areal in Cibitung, from November 2021 until August 2022. This research was arranged in non factorial block complete design with four treatments, consist of P0 (kontrol sub soil), P1 (50% vegetable waste+50% sub soil+Trichoderma sp.), P2 (50% food waste+50% sub soil+Trichoderma sp.) dan P3 (50 rice straw+50% sub soil + Trichoderma sp.). Every treatments repeated 3 times and have 3 samples, so there were 36 seeds. The data was analysis of variance, if test result was significant at 5%, then continued by BNT. The results showed that organic waste could be used as alternative growing media for oil palm nursery, and significantly effected to plant height (3 MAP), stem diameter (2 and 3 MAP), leaf area and biomass. The best treatment based on morphological and physiological response is rice straw and Trichoderma sp.